Planar Polynomial Differential Systems of Degree One: Full Characterization of Its First Integrals - Bilal Ghermoul (International Journal of Differential Equations)
In this work, we classify the first integrals of all planar polynomial differential systems of degree one with real constant coefficients. Additionally, we characterize when these first integrals are either polynomial, or rational, or nonalgebraic.